PENDEKATAN PENDIDIKAN NILAJ SECARA KOMPREHENSIF SEBAGAI SUATU ALTERNATIF PEMBENTUKAN AKHLAK BANGSA - Darmiyati Zuchdi Darmiyati Zuchdi (LPMPP Universitas Negeri Yogyakarta, 2001)
The eclining quality of the Indonesian character needs to be resolved. One of the ways tosolve this problem is through the educational practice, by using a more effective approach.A single approach of values education is considered to be ineffective, that is why it isneeded a comprehensive one. The development of students' personality should be holistic innature, including the intellectual, emotional, and spiritual intelligence. Four importantsubstances of values education are values realization, character education, citizenship education,and moral education. Various programs are needed to help young people develop their